ANALISIS MOTIVASI SISWA KELAS XI DALAM PEMBELAJARAN BIOLOGI MA. PP. HASANATUL BAROKAH TAMBUSAI TIMUR TAHUN PEMBELAJARAN 2014/2015 - Muharni, Yuliana; Afifah, Nurul; Afniyanti, Enny (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
This study aims to determine a class XI student motivation in learning biology MA. PP. Hasanatul Barokah Tambusai Utara. This research is descriptive. The population in this study were all students of class XI MA. PP. Hasanatul Barokah Tambusai Utara totaling 30 people, and the sample in this study is XIA and XIB using saturated sample technique. Data collection techniques used in this study was a questionnaire in the form of Likert scale. the results showed that the motivation of students of class XI IPA MA. PP Hasanatul Barokah Tambusai Timur Learning Year 2014/2015 is in the category of high motivation with the percentage of 82%.